Білім мазмұнын жаңарту жағдайында оқырмандық мəдениетті қалыптастырудың жаңа бағдарлары - Шабажанова, С.К. (My University, 2016)
The article deals with the important problem of the modern society of reading literacy. The authors analyzed the issues of formation of steady interest in reading, reading culture and its role in the formation of a competent person.
Keywords: functional literacy; reading literacy; reading culture; reading competence; motivation for reading